The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/ijms17050721
|View full text |Cite
|
Sign up to set email alerts
|

Design of Acceptors with Suitable Frontier Molecular Orbitals to Match Donors via Substitutions on Perylene Diimide for Organic Solar Cells

Abstract: A series of perylene diimide (PDI) derivatives have been investigated at the CAM-B3LYP/6-31G(d) and the TD-B3LYP/6-31+G(d,p) levels to design solar cell acceptors with high performance in areas such as suitable frontier molecular orbital (FMO) energies to match oligo(thienylenevinylene) derivatives and improved charge transfer properties. The calculated results reveal that the substituents slightly affect the distribution patterns of FMOs for PDI-BI. The electron withdrawing group substituents decrease the FMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…By contrast, for the smallest active compounds (23), the HOMO and LUMO are almost dispersed across the entire molecular region. These results suggest the most active compounds have acceptor-donator behavior, as reported before in several studies [55][56][57][58][59][60][61][62][63].…”
Section: Molecular Orbitalssupporting
confidence: 87%
“…By contrast, for the smallest active compounds (23), the HOMO and LUMO are almost dispersed across the entire molecular region. These results suggest the most active compounds have acceptor-donator behavior, as reported before in several studies [55][56][57][58][59][60][61][62][63].…”
Section: Molecular Orbitalssupporting
confidence: 87%
“…Previous studies demonstrated that frontier molecular orbitals (FMOs) are of critical importance in evaluating candidate compounds for enabling ultrafast interfacial electron transfer. 18,19 In accordance with these findings, computational investigations for the target dye molecules revealed that both HOMO and LUMO orbitals are explicitly localized on the SubPc backbone. The band gap of the compound series increases in the order of SubPc 1 (2.34 eV) < SubPc 2 (2.55 eV) < SubPc 3 (2.71 eV).…”
Section: Table 1 Electrochemical and Optical Properties Of The Subpht...supporting
confidence: 67%
“…Recent advances in p-type organic semiconductors have fulfilled many of the requirements for use in diverse applications; however, n-type materials, needed for diodes, complementary circuits, and solar cells, continue to present challenges. One of the major hurdles remaining is the vulnerability of n-type charge carriers to ambient conditions. So far, the mechanisms by which the electron mobility of organic thin-film transistors (OTFTs) degrades during long-term storage in air (or in other environments that contain oxygen) are still not clear. , de Leeuw et al first discussed this issue and ascribed the drop in mobility to electron trapping by the most common reactive species in an ambient atmosphere, H 2 O, and O 2 .…”
Section: Introductionmentioning
confidence: 99%